Algorithms of training programs for simulator training of ship's engine room personnel - Vlasov A. B. (Vestnik MGTU)
The ship's engine room personnel (mechanics, electromechanics) ensure the technical operation and safe functioning of the ship's power systems. Professional training and retraining of marine specialists of ship's engine rooms is necessary due to the constant improvement of equipment and automation of electric power systems of modern ships. To ensure high-quality training of the ship's engine room team, simulator training is used with a set of modern simulators of ship power plants and electric power systems that meet the standards of the International Convention on Standards of Training, Certification and Watchkeeping for Seafarers. In the course of the study, block diagrams of training algorithms have been developed; program features and examples of their operation have been shown. The obtained algorithms for training on simulators make it possible to implement both the initial training of cadets and the retraining of specialists when improving their qualifications. In the course of simulator practice, the opportunity to develop competencies for working with high-voltage equipment (3–10 kV) of modern ships in accordance with the requirements of the STCW Convention and the STCW Code is of particular importance. Algorithms for training in high-voltage equipment maintenance should be introduced into the educational process to improve the level of qualification of specialists.